Community Empowerment of the Pokdarwis Group through Training on the Utilization of Water Hyacinth as EGO-PURL Compost - Nur Ani; Djatmiko Hidajat; Wartini (IJECS: Indonesian Journal of Empowerment and Community Services, 2025)
ABSTRACT Introduction : Ngargorejo Village, Ngemplak District, Boyolali Regency, the place where the Cengklik Reservoir is located. These reservoirs are the main source of livelihood (fishermen, karamba farmers, tour boat captains, and traders). Based on the SWOT analysis, the condition of Pokdarwis partners has environmental issues related to the very rapid growth of water hyacinths that disrupt the natural ecosystem. The work program appointed is EGO-PURL (Environmental Friendly Fertilizer Water Hyacinth) Fertilizer Manufacturing Training. Objective : Increase the empowerment and knowledge of water hyacinth utilization training participants into, EGO-PURL Compost. Method: This activity involved the Target Partner of Pokdarwis "Kartika" and the Ngargorejo Village Government Partner with, a total of 22 members involved. The activity will be held in July 2025. The activity method uses metacognitive methods which are outlined in the form of lectures, collaborative discussions, and practice. Evaluation was carried out using pretest and pos-tes assessments.  Results: EGO-PALL Fertilizer Making Training, obtained pretest scores to pos-tes which increased by 18 org (81.8%). Where the Mean Pre-test value = 74.6 and the Mean Pos-tes = 95. Conclusion: The results of the evaluation assessment show that there is an increase in knowledge from pre-test scores to pos-tes.  Suggestion: this activity can be developed into an MSME business for the women of the pokdarwis group.       Keywords: Advocacy; EGO-PALL Fertilizer Training; Metacognitive